Pragmatic Analyses of Phraseological Units in Translation - Saparniyazov, Omirbek Nukusbayevich (Journal of Higher Education and Academic Advancement, 2024)
This article provides information on the pragmatic analysis of phraseological units, the establishment of syntactic constructions necessary for the semantics of phraseological units, characterized by the constructive conditionality of their activity, and the determinism of the structure that determines the use of phraseological units. Lexical-grammatical structure of speech units, grammatical structure and verbal complex of phraseological unit-prototype.